Creativity in admissioning students of the National University of San Cristóbal de Huamanga de Ayacucho - Hurtado Ambrocio, Olga (2021)
The research referring to the creativity variable is presented. It is a quantitative, descriptive, comparative investigation by gender, in students entering the Faculty of Education Sciences, in a sample of 62 students, 31 men and 31 women. The sampling was non-probabilistic and intentional. A test on creativity for adults was applied, and the sample was studied, finding that it did not have a normal distribution. Reliability was processed, finding moderate reliability and validation considering the proposal of Artola T. (2012). To test the hypothesis, the SPSS-23 statistical package was used and the data was processed with the Mann-Whitney U statistic, finding that there are significant differences, between men and women,  in graphic creativity and creativity in general and there are no significant differences, between men and women, in the narrative creativity variable.